Caracterização das alterações clínicas e imunopatológicas induzidas pela coinfecção de Leishmania amazonensis e Schistosoma mansoni em camundongos balb/c - Jeferson Kelvin Alves de Oliveira Silva (2020)
Approximately, one billion people are affected by Neglected Tropical Diseases. More than twenty of these diseases are listed by the WHO, and at least twelve among them are caused by parasites, including Leishmaniasis and Schistosomiasis. In Brazil, both of them accounted for approximately 133,100 DALYs (Disability Adjusted Life Years) / 100,000 inhabitants in 2016. Based on data and maps of cutaneous Leishmaniasis and Schistosomiasis geographic distribuition in Brazil, the existence of mutal transmission areas is clearly noticed. Although several studies have shown the consequences of the infection caused by each parasite, the effect of Schistosoma and Leishmania coinfection is mostly unknow, both in experimental models and in human population. Thus, this study aimed to evaluate the clinical, immunopathological and parasitic burden changes associated with experimental infection by Schistosoma mansoni in BALB/c mice previously infected with Leishmania (Leishmania) amazonensis. Therefore, female BALB/c mice were randomly separated into three experimental groups: one monoinfected by L. amazonensis (1x104 metacyclic promastigotes), another by S. mansoni (50 cercariae), and the last one was infected by L. amazonensis and, after three weeks, coinfected by S. mansoni. The animals were evaluated for 15 weeks regarding body weight, evolution of skin lesions and mortality rate were assesed each week. From the fifth week onwards, stool samples were collected from S. mansoni mono and coinfected mice to establish the pre-patent period of schistosomiasis, and after 8 (acute phase) and 12 (chronic phase) weeks of S. mansoni infection, animals from all experimental groups were anesthetized and euthanized to assess parasite burden, pathological changes and immune response. Even after the establishment of Leishmaniasis, S. mansoni infection was able to reduce the inflammation at the infection site and modulate the inflammatory response in the lung and liver tissues. On the other hand, the previous infection by L. amazonensis altered the mice susceptibility to infection by S. mansoni by reducing the number of lung-stage schistosomula and adult worms during the acute phase of the infection. Despite the reduction in the number of worms, the coinfected animals showed more eggs retained in liver during the chronic phase. The coinfected mice showed no significant changes in the mortality rate or liver damage, but it was found that the previous infection by L. amazonensis exerted a protective effect against anemia and weight loss due to acute schistosomiasis. In the lungs of coinfected animals, I was noticed that the protozoan infection reduced the levels of TNF-α, IL-4, IL-5 and IL-17, but increased the chemokines CCL5, CCL24 and CXCL2, resulting in an increased infiltration of eosinophils of netrophils. In the liver, the coinfected animals had higher IL-22 levels than those monoinfected by S. mansoni, with increased eosinophil activity. This resulted in a decrease in the periovular granuloma volume in this group, attenuating the granuloma-associated pathological effects of Schistosomiasis. Therefore, the data showed that coinfection with S. mansoni and L. amazonensis reduced the morbidity associated to both parasites, emphasizing the importance of studying coinfection models, not only to understand general immunopathological processes involved, but also to use them to infer strategies focused on improving the management of these important parasites.